KONFLIK SOSIAL TOKOH DALAM FILM BEYOND OUTRAGE KARYA KITANO TAKESHI (KAJIAN SOSIOLOGI SASTRA) - Kadek Yonita Yona; Anak Agung Ayu Dian Andriyani; Aritonang, Betty Debora (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2023)
This study aims to determine the type of social conflict contained in the film. The data source used in this thesis is a film entitled Beyond Outrage directed by Kitano Takeshi and released in 2012. This thesis is analyzed using the social conflict theory proposed by Lewis A. Coser. Data collection methods and techniques used in this thesis are the method of listening to the advanced technique of note-taking. Data analysis methods and techniques were analyzed using qualitative descriptive methods. Meanwhile, methods and techniques for presenting the results of data analysis using informal methods. The results of the analysis in this thesis, it is found that social conflict consists of two types of social conflict with a total of 4 data. The types of social conflicts are, there are realistic conflicts (2 data) and non-realistic conflicts (2 data).